2004
DOI: 10.1081/fri-200029422
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effluent Wastewater from Abattoirs for Land Application

Abstract: Meat plant wastewater quality depends on water usage, the type of animal slaughtered, and the amount of rendering or processing that is done on site. In Ontario and Quebec, abattoir wastewater total chemical oxygen demand (TCOD) ranged from 2333 to 8627 mg/L, and suspended solids (SS) from 736 to 2099 mg/L, volatile suspended solids (VSS) represented 80% of SS, and protein content varied from 444 to 2775 mg/L. Nitrogen (N) and potassium (P) averaged 6.0 and 2.3 g/100 g of TCOD, respectively. Ammonia and sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 38 publications
3
55
0
Order By: Relevance
“…[38]. Most small and medium abattoirs do not have the tertiary and advance treatment facilities, due to high capital involved in these methods [31,38].…”
Section: High Costmentioning
confidence: 99%
See 2 more Smart Citations
“…[38]. Most small and medium abattoirs do not have the tertiary and advance treatment facilities, due to high capital involved in these methods [31,38].…”
Section: High Costmentioning
confidence: 99%
“…Wastewater carries diverse microbes that can contaminate the water sources [42], leading to the spread of pathogens from one place another [31]. This may lead to a wide range of diseases such as cholera, typhoid, and dysentery [43].Wastewater discharges from slaughterhouse without proper disinfection, leads to occurrence of meat based infections due to the high populations of E. coli and Salmonella sp.…”
Section: Disease Causing Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Since slaughterhouse wastewater has high chemical constituents loading and is made up of about 45% soluble and 55% coarse suspended organics (Nunez and Martinez 1999), some municipalities impose surcharges on treating slaughterhouse wastewater. Meat plant wastewater quality depends on water usage, type of animal slaughtered, and the amount of rendering or processing done on site (Mittal 2004). In Ontario and Quebec, Canada, slaughterhouse wastewater COD ranged from 2333 to 8627 mg/L, and SS from 736 to 2099 mg/L, volatile suspended solids (VSS) represented 80% of SS, and protein content from 444 to 2775 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Stebor et al (1990) reported that 400 to 3100 L of wastewater was generated per animal. In general, poultry slaughtering operations use more water, producing lower strength of the wastewater (Mittal 2004).…”
Section: Introductionmentioning
confidence: 99%